INNOVATIVE BASIS CREATING THE FOUNDATION FOR THE THIRD RENAISSANCE IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
The greatest foundation for the emergence of the Third Renaissance, the formation of a new Uzbekistan and the emergence of new unique ideas, the training of a new generation to look into a completely different world, the conditions created for young scientists to realize their inner talents, intelligence and reforms in science and education.